2015
DOI: 10.1016/j.jcma.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

High neuroendocrine component is a factor for poor prognosis in gastrointestinal high-grade malignant mixed adenoneuroendocrine neoplasms

Abstract: The predominant tumor component in primary tumors was a prognostic factor and could predict tumor emboli and liver metastases pathology in high-grade malignant MANECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 16 publications
4
33
1
Order By: Relevance
“…Nevertheless, metachronous metastases are rarely biopsied, and nuclear medicine tools cannot help distinguishing between adenocarcinoma and PDNEC because, for example, both components display 18 FDG positron-emitting tomography positivity, and negative somatostatin receptor scintigraphy due to lack of somatostatin receptors expression [83] . The cell type present in tumour emboli on resected primary tumours may be similar to that found in lymph node and distant metastases; thus, its analysis could be an alternative to metastasis biopsy [22] .…”
Section: Management Of Minenmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, metachronous metastases are rarely biopsied, and nuclear medicine tools cannot help distinguishing between adenocarcinoma and PDNEC because, for example, both components display 18 FDG positron-emitting tomography positivity, and negative somatostatin receptor scintigraphy due to lack of somatostatin receptors expression [83] . The cell type present in tumour emboli on resected primary tumours may be similar to that found in lymph node and distant metastases; thus, its analysis could be an alternative to metastasis biopsy [22] .…”
Section: Management Of Minenmentioning
confidence: 93%
“…Highgrade MiNEN generally combine a non-neuroendocrine carcinoma (usually adenocarcinoma, but possibly squamous-cell carcinoma or acinar-cell carcinoma in the pancreas as mentioned above) or an adenoma (villous or tubulo-villous) with a PDNEC component, which is generally more aggressive [20][21][22][23][24] . The prognosis of intermediate-grade MiNEN is generally determined by the non-neuroendocrine component rather than the G1 or G2 NET component.…”
mentioning
confidence: 99%
“…14,15 Some authors have suggested that the prognosis of digestive MANECs is determined by the most aggressive histologic component. 1,15 Chen et al 30 recently demonstrated that a high volume of high-grade NET (.50% of the total tumoral volume) is an independent predictor of poor prognosis in digestive MANECs. Expression of CD117 detected by immunohistochemistry correlates with a worse prognosis in colorectal MANECs, but it is uncertain whether this is true for biliary MANECs.…”
Section: Immunohistochemical and Ultrastructuralmentioning
confidence: 99%
“…20,25 However, information on follow-up is limited to 11 cases, many of which report follow-up intervals of 12 months or less. 19,20,24,25,27,28,30 Kim et al 31 found that prognosis of biliary MANECs is very poor and comparable with pure NET grade 3, with a disease-free survival of 5.3 months, overall survival of 12.2 months, and 0 of 7 patients alive after 2 years.…”
Section: Immunohistochemical and Ultrastructuralmentioning
confidence: 99%
“…3,6 These characteristics make mixed adenoneuroendocrine carcinomas diagnostically challenging, as only appropriate immunohistochemical screening for neuroendocrine differentiation may reveal the tumor's dual nature. 3 Clinically, colorectal mixed adenoneuroendocrine carcinomas are usually aggressive neoplasms, [7][8][9] with a clinical need for intensified treatment strategies. However, even if the dual nature of these tumors is fully recognized, there exists no unifying concept of how to treat colorectal mixed adenoneuroendocrine carcinoma patients.…”
mentioning
confidence: 99%